2011
DOI: 10.1021/om2005832
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Transfer Hydrogenation Catalysis by B(C6F5)3

Abstract: The activation of amines by B(C6F5)3 is shown to effect the catalytic racemization of a chiral amine. Extending this strategy to a bimolecular process, catalytic transfer hydrogenation of imines, enamines, and N-heterocycles is demonstrated using iPr2NH as the source of hydrogen and a catalytic amount of the Lewis acid B(C6F5)3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
82
0
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 47 publications
1
82
0
9
Order By: Relevance
“…[30] It is well established that B(C 6 F 5 ) 3 is able to abstract hydride from amines in the a-position to nitrogen. [31] Stephan et al [32] observed that secondary amines undergo racemization upon treatment with the Lewis acid B(C 6 F 5 ) 3 , and further developed this into a B(C 6 F 5 ) 3 -catalyzed transfer hydrogenation of imines, enamines, quinolines, and aziridines using diisopropylamine as the hydrogen source (Scheme 6).…”
Section: Hydrogen Splitting and Metal-free Hydrogenationmentioning
confidence: 99%
“…[30] It is well established that B(C 6 F 5 ) 3 is able to abstract hydride from amines in the a-position to nitrogen. [31] Stephan et al [32] observed that secondary amines undergo racemization upon treatment with the Lewis acid B(C 6 F 5 ) 3 , and further developed this into a B(C 6 F 5 ) 3 -catalyzed transfer hydrogenation of imines, enamines, quinolines, and aziridines using diisopropylamine as the hydrogen source (Scheme 6).…”
Section: Hydrogen Splitting and Metal-free Hydrogenationmentioning
confidence: 99%
“…Transfer hydrogenations of ketones, aldehydes, and imines can be achieved by the classic Meerwein-Ponndorf-Verley protocol, catalyzed by a variety of transition metal complexes and more recently by FLPs (38). In contrast, transfer hydrogenation of olefins has received much less attention.…”
Section: N (H)sir 3 ]mentioning
confidence: 99%
“…We thus accomplished the transfer hydrogenation of imines (Scheme 1, top). [10,13] Theapplication of this approach to alkenes is aworthwhile goal as it would allow for the transfer of dihydrogen from one unsaturated hydrocarbon to another unsaturated hydrocarbon in aprocess that is catalyzed by amain-group Lewis acid (Scheme 1, bottom). [14,15] However,t he involvement of carbenium ions at different stages of this process is likely to provoke cationic oligomerization of both reaction partners.It must be mentioned that Stephan and co-workers recently reported one example of aB (C 6 F 5 ) 3 -catalyzed alkene hydrogenation that required assistance by Et 2 Oa saL ewis basic component.…”
mentioning
confidence: 99%